Improving Students' Speaking Skill Using Fable Pictures Cued And Storytelling Technique - Theresia N Saragih; Putri Roza Afsari Saragi; Indriani (Universitas Maritim Raja Ali Haji (UMRAH), 2023)
This research used a storytelling technique with fable pictures to help students develop their speaking skills in learning English. Classroom Action Research is used in this study, which is applied in the classroom to see how the students' ability to speak English consists of 10 students from SMA Negeri 1 Sidamanik in the academic year of 2021/2022, North Sumatra. This research showed that the storytelling technique with fable pictures cued could be a helpful method for students in the classroom. Students seemed to have the confidence to speak without being nervous. Also, they enjoyed the fabled story with the picture. The pre-cycle results were 78.0, and cycle 1 increased by 2. 46. In cycle 2, the improvement score received was 5.04, and to combine all the improvements per cycle, which is 7.5. the researchers can conclude that telling stories with pictures cued can improve students' speaking ability.